Comparative Analysis of Stock Returns and Trade Volume Activity Based on Trump's Policy Announcement on Industrial and Textile Sector Companies Listed on LQ-45 - Sultan, Nurul Fahmi (STIE AMKOP, 2025)
This study is a quantitative study that aims to determine the difference between average stock returns and trade volume activity before and after the announcement of Trump's export tariff policy. This research was conducted with a time of 10 days, namely 5 days each before and after the announcement date. The population of this study is industrial and textile sector companies listed in LQ-45 as many as 5 companies. The sample selection method used is the purposive sampling technique with certain criteria. The data testing techniques used were descriptive analysis, normality test, and paired sample t-test. The results of this study are that there is no significant difference in average stock returns and trade volume activity before and after the announcement of Trump's export tariff policy in Indonesia.